2015
DOI: 10.1161/atvbaha.115.306108
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Causal Candidate Genes in Coronary Artery Disease Loci

Abstract: Objective Genome-wide association studies (GWAS) have so far identified 159 significant and suggestive loci for coronary artery disease (CAD). We now report comprehensive bioinformatics analyses of sequence variation in these loci to predict candidate causal genes. Approach and Results All annotated genes in the loci were evaluated with respect to protein coding SNPs and gene expression parameters. The latter included expression quantitative trait loci, tissue specificity, and miRNA binding. High priority ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 59 publications
0
119
0
1
Order By: Relevance
“…annot., bioinformatics annotation according to Braenne et al (2015) or others (Musunuru et al , 2010; Salvi et al , 2013); no data, no eQTL data or non‐coding variant; NA, not analysed.…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
See 2 more Smart Citations
“…annot., bioinformatics annotation according to Braenne et al (2015) or others (Musunuru et al , 2010; Salvi et al , 2013); no data, no eQTL data or non‐coding variant; NA, not analysed.…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…Indeed, annotation of the risk alleles revealed that the majority are located in chromosomal regions relevant for gene regulation. The identification of the underlying pathophysiological mechanism(s) thus requires annotation of the affected gene(s), which may be challenging (Braenne et al , 2015). The chromosome 9p21 locus is a prominent example: whereas initial studies focused on the two genes situated at the locus, CDKN2A and CDKN2B, current studies rather point to radically new disease mechanisms.…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The genetic analysis of gene expression by identification of expression quantitative trait loci (eQTLs) in relevant tissues has proven useful to predict candidate genes at GWAS loci and biological pathways that are perturbed in affected individuals. [3][4][5][6] Subcutaneous adipose tissue serves as a buffering system for lipid energy balance, particularly fatty acids, 7,8 and might play a protective role in metabolic and cardiovascular disease risk. 9 Subcutaneous adipose eQTL studies have implicated genes involved in obesity and metabolic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Using network centrality analysis, they identified several novel gene candidates involved in CAD pathways. In a second CAD study, Braenne et al 18 performed a comprehensive bioinformatics analysis of sequence variation in known CAD loci to predict candidate causal genes. This led to a revised list of gene candidates for CAD and the expansion of the CAD genetic landscape.…”
Section: The Post-gwas Era: Functional Validation Of Snps Associated mentioning
confidence: 99%